Predictive analysis of waste generation at the Babussalam Islamic Boarding School, Pekanbaru City - Rabillah Fathur Rahman; Yulia Fitri; Shabri Putra Wirman (Lembaga Studi Pendidikan dan Rekayasa Alam Riau, 2023)
Babussalam Islamic Boarding School is an Islamic educational institution that has education levels ranging from kindergarten, elementary school, junior high school, and high school with a population of students, teachers, and employees in the Islamic Boarding School of Babussalam which is 2248 people. A large population with an area available produces waste generation (organic, paper, and plastic). Research has been conducted related to the generation of waste generated in the Babussalam Islamic Boarding School and the predictions for the next five years. Measurement methods and data calculations use SNI 19-3964-1994. Total solid waste generation in Pesantren Babussalam is 0.3746 kg/person with an average of 0.042 kg/person. The total volume of solid waste generation in Pesantren Babussalam is 98.338 liter/person with an average of 1.37 liter/person. The average composition of organic waste is 0.1392 kg/person with a percentage of 37%. The average composition of waste paper is 0.1374 kg/person with a percentage of 36%. The average composition of plastic waste is 0.1042 kg/person with a percentage of 27%. Waste generation in 2024 is predicted to increase by 35.33371 kg/year, with a total generation in 2024 of 176.668 tons.